Reclaiming Artistic Research - Cotter, Lucy 1973- (Berlin Hatje Cantz, 2024)
Reclaiming Artistic Research – Expanded Second Edition (2024) explores artistic research in dialogue with 24 artists worldwide and embraces artists’ dynamic engagement with other fields. Reclaiming the term “artistic research” from its academic associations, the book foregrounds the material, spatial, embodied, organizational, choreographic, and technological ways of knowing and unknowing specific to contemporary artistic inquiry. Through in-depth dialogues, the book seeks to articulate the dynamic nature of artistic thinking in practice, tracing how ideas and forms co-emerge through material, conceptual and embodied ways of working.The second expanded edition of this acclaimed book features four new artist dialogues and a new essay by Lucy Cotter entitled “Artistic Research in a World on Fire” that reflects on the changing stakes of artistic research in the wake of the global pandemic, a widespread reckoning with social justice and equity, the growing role of artificial intelligence, and the urgent reality of climate change. Foregrounding art’s engagement with multiple fields, Reclaiming Artistic Research manifests how artists produce new paradigms and questions, rather than supplementing existing (academic) knowledge.The book embraces contemporary art’s multisensory modes of witnessing and highlights how artists’ gathering and creation of material, textual, and embodied sources of knowledge can support the decolonization of knowledge, the centering of Indigenous ways of knowing, and the creation of greater accessibility to knowledge. Through radical archival interventions and oral-material creations, many featured artists find ways to manifest and engage with the fragmentation and dispersal of human histories in ways that the discipline of history struggles (and often fails) to do. This matters in a world in which marginalized peoples, enslaved and disappeared peoples, and those who have faced forced migrations, genocide, and extinction seek to claim their own histories and trajectories.Several artists in Reclaiming Artistic Research engage the ethical and social repercussions of emerging technologies in provocative and publicly accessible ways. The dialogues offer insight into artists’ intimate relationship with media, which encompasses the ability to repurpose existing technologies for critical and unforeseen possibilities. Building on the book’s original twenty dialogues with artists worldwide, the new dialogues engage with US-based artists Stephanie Dinkins, Cannupa Hanska Luger, Yo-Yo Lin, and Richard Mosse, whose practices attend to questions of human and nonhuman survival, self-care, and collective care, new technologies, and the unlearning of ableist, gendered, sexist, and racist paradigms.Cannupa Hanska Luger’s ongoing Future Ancestral Technologies project imagines past the exodus of the wealthy to other planets to consider adaptations necessary for the future survival of Earth. Stephanie Dinkins’s interactive and immersive works create models for reorienting AI and emerging technologies toward social benefit, equity, and collective care. Richard Mosse’s recent film Broken Spectre repurposes multispectral technologies and UV microscopy photography to create one of the most extensive documents of the Amazon rainforest destruction in existence. Yo-Yo Lin leans into transcultural and queer imaginaries around the body, incorporating chronic pain, illness, and disability to co-shape expanded forms of collective knowledge.
Keywords: Artistic research